Rapid green preparation of Lu7O6F9:RE (RE = Eu3+/Gd3+, Yb3+/Er3+) phosphors using ionic liquids. Issue 12 (15th June 2023) - Sun, Qi; Xiao, Xue; Zhang, Xiangting; Song, Yanhua; Zhou, Xiuqing; Sheng, Ye; Zheng, Keyan; Zou, Haifeng
Abstract: Rare earth oxyfluoride materials are a fascinating class of host matrixes for various applications. However, rapid green preparation of multifunctional rare earth oxyfluoride phosphors remains a huge challenge. In this work, we report the fast synthesis of Lu7 O6 F9 using ionic liquids (ILs), which enables the precursors to be obtained at 10 min. The effects of calcination temperature, reaction temperature, reaction time and fluorine source on the phase and morphology of precursors and products are elaborated and the growth mechanism is put forward. Eu 3+ alone and Yb 3+, Er 3+ co-doped samples were prepared to investigate the down-conversion (DC) and up-conversion (UC) properties, respectively. Besides, Gd 3+ ions were introduced to the Eu 3+ doped products, endowing the phosphors more intense luminescence and paramagnetic properties. The proposed facile synthesis route, excellent luminescence, thermal stability and paramagnetic properties open up the way to obtain rare earth fluoride and oxyfluoride for multifunctional applications.